Antiproliferative effects of carbon monoxide on pancreatic cancer - Vítek, Libor; Gbelcová, Helena; Muchová, Lucie; Váňová, Kateřina; Zelenka, Jaroslav; Koníčková, Renata; Suk, Jakub; Zadinova, Marie; Knejzlík, Zdeněk; Ahmad, Shakil; Fujisawa, Takeshi; Ahmed, Asif; et al. (Digestive and liver disease, 2014)
BACKGROUND: Carbon monoxide, the gaseous product of heme oxygenase, is a signalling molecule with a broad spectrum of biological activities. The aim of this study was to investigate the effects of carbon monoxide on proliferation of human pancreatic cancer. METHODS: In vitro studies were performed on human pancreatic cancer cells (CAPAN-2, BxPc3, and PaTu-8902) treated with a carbon monoxide-releasing molecule or its inactive counterpart, or exposed to carbon monoxide gas (500 ppm/24h). For in vivo studies, pancreatic cancer cells (CAPAN-2/PaTu-8902) were xenotransplanted subcutaneously into athymic mice, subsequently treated with carbon monoxide-releasing molecule (35 mg/kg b.w. i.p./day), or exposed to safe doses of carbon monoxide (500 ppm 1h/day; n = 6 in each group). RESULTS: Both carbon monoxide-releasing molecule and carbon monoxide exposure significantly inhibited proliferation of human pancreatic cancer cells (p<0.05). A substantial decrease in Akt phosphorylation was observed in carbon monoxide-releasing molecule compared with inactive carbon monoxide-releasing molecule treated cancer cells (by 30-50%, p<0.05). Simultaneously, carbon monoxide-releasing molecule and carbon monoxide exposure inhibited tumour proliferation and microvascular density of xenotransplanted tumours (p<0.01), and doubled the survival rates (p<0.005). Exposure of mice to carbon monoxide led to an almost 3-fold increase in carbon monoxide content in tumour tissues (p=0.006). CONCLUSION: These data suggest a new biological function for carbon monoxide in carcinogenesis, and point to the potential chemotherapeutic/chemoadjuvant use of carbon monoxide in pancreatic cancer.
Keywords: duktální karcinom slinivky břišní; Carbon Monoxide; Anticancer effects; Cell Proliferation; fosforylace; Xenograft Model Antitumor Assays; Phosphorylation; myši nahé; Carcinoma, Pancreatic Ductal; protoonkogenní proteiny c-akt; Proto-Oncogene Proteins c-akt; Gasotransmitters; Heme catabolic pathway; Organometallic Compounds; Pancreatic Neoplasms; xenogenní modely - testy protinádorové aktivity; Animals; lidé; Humans; zvířata; nádory slinivky břišní; gasotransmitery; myši; Heme oxygenase; proliferace buněk; Mice, Nude; Mice; oxid uhelnatý; organokovové sloučeniny